Ductile to brittle fault zone evolution in Austroalpine units to the southeast of the Tauern Window (Eastern Alps) - Wölfler, A.; Frisch, W.; Fritz, H.; Danisik, Martin; Wölfler, A. (Birkhauser Verlag AG, 2015)
© 2015 Swiss Geological Society This study combines structural and thermochronological analysis with published geochronological data to evaluate the tectonic evolution of the ductile Main Mylonite Zone and the adjacent brittle Ragga–Teuchl fault to the southeast of the Tauern Window. The Main Mylonite Zone experienced ductile deformation with top-to-the-NW transport direction. From microstructural analysis and published K/Ar and Ar/Ar data the timing for this ductile deformation is proposed to be Late Cretaceous in age, contemporaneous to a well documented extensional collapse that affected large parts of the Eastern Alps. Subsequent brittle faulting affected the Main Mylonite Zone and neighbouring units. Apatite fission track data suggest that brittle deformation along the Ragga–Teuchl fault and adjacent units occurred in the middle- and late Miocene (~23 and ~11 Ma), contemporaneous with the main phase of lateral extrusion. Our results show that a rather small study area may comprise information about the evolution of the Eastern Alps from Late Cretaceous to late Miocene times. We also demonstrate that low-temperature thermochronology is a viable tool to resolve the timing of brittle faulting and accompanied fluid activity.